Casa de tèranga: nomeações e materialidades da migração transnacional entre Senegal e Brasil - Santos, Frederico Santos dos (2022)
The Senegalese present on the streets of the city of Passo Fundo (RS/Brazil) have called my attention since 2010, when I joined the University of Passo Fundo as a professor. By attending Sunday muslim meetings, I realized the challenges of these displacements in living long years away from my family. The argument that I develop in this thesis is that the Senegalese family is constituted in the displacements of the subjects, from the materialities of the relationships and naming processes, in the tangle of places inhabited in their settlements, in which the tèranga (which can be translated as hospitality and honor) is a fundamental element, more than the house as a physical space. The field research was developed as a multi-sited ethnography, having two territories as a starting point, Passo Fundo (RS/Brazil) and Dakar (Senegal), but it was not restricted to them. In Brazil, it was carried out from Passo Fundo, accompanying the Senegalese in Porto Alegre and São Paulo (from January to August 2019), and in Senegal (from September 2019 to March 2020), departing from Dakar, traveling across 9 cities. Ethnography continued as a mesh, from the notion revisited by Ingold in the reticular trails left by the Senegalese as they follow their life in the keur (house), in their places of settlement, with multiple entanglements, with apparent permanence and solidity, in an ecceity experienced in the panoramas and transitions taken by the inhabitants.